The Effects of Voice and Visible Speaker Change on Memory for Spoken Words - Sheffert, S.M.; Fowler, C.A. (Journal of memory and language, 1995)
Recent research suggests that voice information is not discarded during word recognition, but is represented in memory and can serve as a retrieval cue for word recognition. The research reported here asks whether other idiosyncratic aspects of an event in which speech occurs are also retained with speech in memory. Four experiments explored the effects of voice and visible speaker change on spoken word recognition. In each experiment, subjects watched a videotape of speakers producing words. When a word was repeated, the visible speaker, his or her voice, and a feature of wearing apparel were either the same or different from the first presentation. Subjects made recognition judgments based on word identity and characteristics of the speaker. The results indicate that the memory subserving spoken word recognition includes detailed information about a talker′s voice and face, but that each is preserved differently.